A FUNÇÃO SIMBÓLICA E SEUS DESVIOS: DESAFIOS IMPLICADOS NA RELAÇÃO ENTRE DESEJO, LEI E VIOLÊNCIA - Guerra, Alba Gomes; Carvalho, Glória (Cadernos de Linguagem e Sociedade, 2010)
On the basis of empirical data, the theme of violence is brought into discussion. Supported by Lacan’s ideas as our theoretical background, the concept of the paternal fatherlike/symbolic role stands out as it interdicts the omnipotence of desire. In addition, the consequences of such an omnipotent desire, in its transgresssive nature, have been taken as implying a destructive result generated within the social realm, and returning to it on account of its totalitarian/omnipotent/immoderate character.